Principal-Agent Problem in the Theory of Discrimination - Do HR Managers Discriminate More Than Business Owners? - Froňková, Pavlína (2015)
Becker's discrimination theory predicted that the discrimination by employers on competitive markets should cease to exist. However, in past decades, it was shown that discrimination on the labour market is a prevalent phenomenon. In this thesis I analyse what is the impact of agency problem on the theory of discrimination. I show that when an agent (in the thesis called 'agent employer') is deciding whether to employ or not to employ a worker, his motivation is different compared to principal's. The outcome of the analysis is such that under certain assumptions, the agent employer with non-zero taste for discrimination will always choose to discriminate.